2020
DOI: 10.1167/tvst.9.4.10
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Central Drusen Volume and Low-Luminance Deficit in Age-Related Macular Degeneration

Abstract: Citation: Ou WC, Denlar RA, Csaky KG. The relationship between central drusen volume and low-luminance deficit in age-related macular degeneration. Trans Vis Sci Tech. 2020;9(4):10, https://doi.org/10. 1167/tvst.9.4.10 Purpose: To determine the relationship between central drusen volume and lowluminance deficit (LLD) in visual acuity (VA) in patients with intermediate age-related macular degeneration (AMD). Methods:In this cross-sectional study, 42 patients with intermediate AMD underwent testing for VA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…Coincidentally, our HRF group also had a higher mean central drusen volume. In our secondary analysis adjusting for the presence and absence of HRF, cube-root transformed central drusen volume was found to be associated with LLD measurement, which was in contrast to our prior study showing no such correlation in eyes with iAMD [9]. In our previous study, the presence of HRF was not evaluated, so it was possible that the lack of adjustment for HRF accounted for the negative finding.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Coincidentally, our HRF group also had a higher mean central drusen volume. In our secondary analysis adjusting for the presence and absence of HRF, cube-root transformed central drusen volume was found to be associated with LLD measurement, which was in contrast to our prior study showing no such correlation in eyes with iAMD [9]. In our previous study, the presence of HRF was not evaluated, so it was possible that the lack of adjustment for HRF accounted for the negative finding.…”
Section: Discussioncontrasting
confidence: 97%
“…Neely et al [8] found that in eyes with early AMD, dark adaptation was significantly delayed in eyes with SDD as compared to eyes without SDD, but the difference was no longer statistically significant after adjusting for age. In addition, Ou et al [9] did not find a correlation between central drusen volume and low luminance deficit in eyes with iAMD. However, Ou et al [10] did detect statistically significant differences between controls and intermediate/advanced (non-neovascular) AMD eyes in both normal and low luminance quantitative contrast sensitivity function (qCSF), as measured in area under log CSF (AULCSF).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, different from eyes with SDDs, it remains unknown whether the function of the retina changes with an increased soft drusen load; a study demonstrated that, functionally, the amount of drusen within the central 3 mm of the macula does not appear to be related to low-luminance deficit in intermediate AMD [ 35 ].…”
Section: Stratifying the Risk Of Advanced Amd: Emerging Drusen Subtyp...mentioning
confidence: 99%